PENGUATAN KECERDASAN SPIRITUAL TERHADAP PENGARUH INVESTIGATIVE AUDIT, DATA MINING, DAN CONTINUOUS AUDIT DALAM PENDETEKSIAN FRAUD - Indah Tri Hartini; Muh. Wahyuddin Abdullah; Andi Wawo (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to examine the effect of investigative audits, data mining, and continuous audits on fraud detection by strengthening spiritual intelligence at BPKP Representatives of South Sulawesi Province. To support the research objectives, researchers used three main theories, namely the hexagonal fraud theory, agency theory, and attribution theory. This study is quantitative and takes a causality approach. The population in this study were auditors who were representatives of the South Sulawesi provincial financial and development oversight agency and had conducted investigative audits. The technique for selecting the sample used a purposive sampling method with a total of 36 people. Multiple linear regression analysis and moderated regression analysis with an absolute difference value approach are used in the hypothesis testing method. The statistical analysis was carried out using the SPSS 25 application program. The test results in this study indicate that investigative auditing and data mining have a significant effect on fraud detection. Meanwhile, continuous auditing has no significant effect on fraud detection. Moderation analysis carried out proves that the moderating variable of spiritual intelligence is not a reinforcing variable in the interaction of investigative audit, data mining, and continuous audit influences on fraud detection.